The Poetics of Grief and Healing in Nadin Amizah’s ‘Bertaut’ : A Stylistic Analysis - Nur Abqori Salma; Otong Setiawan Djauhari (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2025)
This study explores the intricate relationship between grief and healing as depicted in Nadin Amizah's song "Bertaut." Through a stylistic analysis, the research delves into the poetic elements employed by Amizah to convey the emotional depth of loss and the journey towards recovery. By examining the use of imagery, metaphor, and lyrical structure, the paper highlights how these stylistic choices enhance the listener's understanding of the complexities of grief. Furthermore, the analysis reveals the transformative power of music as a medium for expressing sorrow and facilitating healing. Ultimately, this study contributes to the broader discourse on the role of art in processing emotional experiences, emphasizing the significance of Amizah's work in contemporary music.